KONSUMSI SERAT, KALIUM DAN HUBUNGANNYA DENGAN KADAR LOW DENSITY LIPOPROTEIN (LDL) PASIEN PENYAKIT JANTUNG KORONER - Yuliantini, Emy (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Changing patterns of human life cause various diseases, such as infectiousdiseases and malnutrition to degenerative diseases, including heart disease(cardiovascular). One of the major risk factors of cardiovascular diseases characterized byelevated levels of total cholesterol and LDL cholesterol. Fruits and vegetables are also animportant part of the diet to prevent cardiovascular disease, by providing vitamins,minerals, fiber and potassium. This research was conducted in Poly of Cardio HospitalOutpatient Dr.M.Yunus design used was observational analytic with cross-sectionalapproach. Sampling by means of purposive sampling with a sample numbering 81 people.Data consumption of fiber and potassium patients obtained by filling out a form semiquantitativeFFQ is eaten last month. The results showed that there is a relationshipbetween fiber intake (p-value = 0.001), the consumption of potassium (p-value = 0.000)with LDL cholesterol levels in outpatients at Poly of Cardio Dr. M. Yunus Bengkulu.Nutritionist in collaboration with Doctors and Nurses in Heart Poli Dr. M YunusBengkulu in the form of consultation and counseling when CHD patients examinationevery month.